Desarrollo de un simulador de nivel de enlace del estándard AFDX - Villegas, Javier; Fortes-Rodríguez, Sergio; Baena-González, José Carlos; Baena-Martínez, Eduardo; Ortiz, Rafael; Colomer, Benjamín; Barco-Moreno, Raquel (My University, 2020)
This paper presents a link level implementation of a system-level Avionics Full-Duplex Switched (AFDX) network simulator. The simulator features two main elements, the End-System and the AFDX switch. It is proposed as a tool for validation and optimization which would allow faster development of new network topologies, serving as well as a base for future simulation instruments.
Keywords: Aviónica; Aeronáutica - Sistemas de comunicaciones; Simuladores; AFDX; Simulation; Matlab; Switched; Networks